1993
DOI: 10.1002/j.1460-2075.1993.tb06200.x
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of hematopoietic development from embryonic stem cells by antisense vav RNA.

Abstract: The vav proto‐oncogene is universally and specifically expressed in hematopoietic cells. vav contains a unique array of motifs allowing the protein to function as a signal transducer and possibly as a transcription factor. Under certain in vitro culture conditions murine embryonic stem cells develop into colonies containing multiple hematopoietic lineages. In embryonic stem cell lines, constitutively expressing high levels of antisense vav transcripts through a stably integrated transgene, differentiation into… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
1

Year Published

1995
1995
1999
1999

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(35 citation statements)
references
References 33 publications
1
33
1
Order By: Relevance
“…A random hexamer-primed cDNA strand was synthesized with mouse mammary leukemia virus RT. The RT products were used as templates for PCR amplification by using gene-specific primers (35,64,68). The amount of cDNA synthesized was calibrated by using the relative expression level of hypoxanthine phosphoribosyltransferase (HPRT) as a standard.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A random hexamer-primed cDNA strand was synthesized with mouse mammary leukemia virus RT. The RT products were used as templates for PCR amplification by using gene-specific primers (35,64,68). The amount of cDNA synthesized was calibrated by using the relative expression level of hypoxanthine phosphoribosyltransferase (HPRT) as a standard.…”
Section: Methodsmentioning
confidence: 99%
“…The results described above point to the participation of Shp-2 in controlling the development of the myeloerythroid lineages. To corroborate the in vitro colony assays, we examined the expression of several genes that serve as markers of hematopoietic cells by RT-PCR analysis (35,64,68). Total RNAs of wild-type and mutant origins were isolated from ES cells and from EBs collected at selected days.…”
Section: Downloaded Frommentioning
confidence: 99%
“…In this regard, one molecule of potential interest is the 95-kDa product of the Vav protooncogene, another SH2 domain-containing protein which, like PTP1C, has been identified in all hemopoietic lineages and implicated by several lines of evidence in the control of hemopoietic cell growth and differentiation (18 -20). Inhibition of Vav expression, for example, interferes with development of hemopoietic cells from embryonic stem cells (21), and, as is consistent with its participation in a broad range of hemopoietic cell signaling pathways, Vav has been shown to become tyrosine-phosphorylated following cross-linking of antigen receptors on lymphocytes (22)(23)(24), Fc␥ and ⑀ receptors on monocytes and mast cells, respectively (24,25), and c-kit receptors on multiple hemopoietic lineages (26,27). Vav contains a number of structural motifs found in many signaling effectors, including an SH2, a pleckstrin homology, and two SH3 do-* This work was supported in part by grants from the Medical Research Council of Canada and the National Cancer Institute of Canada (NCIC) and by the Health Canada Bureau of Drug Research.…”
mentioning
confidence: 86%
“…The phosphorylation of Vav has been observed after stimulation of the T-cell receptor (Gulbins et al 1993), membrane immunoglobulin (Gulbins et al 1994c), Fc receptor (Margolis et al 1992), interferon receptor (Platanias & Sweet 1994), c-kit (Alai et al 1992), PRLr (Clevenger et al 1995b), and the receptors for IL-1 (Gulbins et al 1994a) and -2 (Evans et al 1993). Antisense experiments have revealed that the inhibition of Vav expression in embryonic stem cells prevents their in vitro differentiation into mature hematopoietic elements (Wulf et al 1993). These findings, however, have been contradicted in a recent study using vav / mouse embryonic stem cells (Zhang et al 1994), as normal hematopoietic differentiation was observed in this system in vitro.…”
Section: Mediators Of Prl-induced Lymphocyte Proliferation -Vavmentioning
confidence: 99%